PELAKSANAAN RESES OLEH ANGGOTA DPRD KOTA BATAM PERIODE (2014-2019) TAHUN 2015 (Studi Dapil 1: Kecamatan Bengkong dan Kecamatan Batu Ampar) - Dian Maharani; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Recess as one of aspirations distribution with upward vertical from the people to the government, either through the visit of the Legislative Council (DPRD) to the Electoral District (Dapil) to its constituents. However, the implementation of the recess conducted by Batam City council Dapil 1 is still less than optimal. Members of Legislative Council (DPRD) in the recess was conducted in groups, it wasn’t like the other dapil which conducted by individually so that the recess looked like finished only with ceremonial in the implementation of recess, it should be 9 (nine) of legislative members who attended the recess from various commissions were more constituent in accommodating the aspirations from the people.The purpose of this study are: How was the implementation of recess going, whom conducted by members of Legislative Council (DPRD) Batam City (2014-2019) period in 2015? And what were the supporting factors and inhibitors factors in the implementation of the recess whom conducted by the members of Batam City Council (2014-2019) period in 2015? This research is using the theory of representation of aspiration and physical representation. The type of research that the authors use which is, Descriptive Research.The results showed us that the recess has been provided for use as a means to communicate and directly approach the constituents in it is area, still needs some a certain of creativity that can provide and create an interesting nuance to the public’s attention. This far, the recess whom conducted by members of Batam City Council is only used as an annual periodic routine which is not clear on its follow –up and the level of effectiveness of its implementation. The supporting factors in the implementation of recess is the moral and political support of the Councils, holding public forums. The inhbiting factors in recess implementation is the relation between representatives of Batam City Council with Constituents in dapil 1, the lack of constituents confidence in the credibility of Legislative Council (DPRD) members and the attitude of selfishness of the Council and society.Keywords : Implementation, Recess of members Legislative Council (DPRD) of Batam City.